A lithium cobalt oxide positive electrode material and preparation method thereof
By adopting a double-clad structure on the lithium cobalt oxide positive electrode material, the first cladding layer composited by fast ion conductor and carbon nanotube and the second cladding layer of metal compound layer are solved, and the problem of instability of the material at the surface under high voltage is achieved, achieving higher magnification, storage performance and capacity.
Patent Information
- Application Number
- CN202310010879.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-01-03
AI Technical Summary
The existing lithium cobalt oxide positive electrode material acts with the electrolyte at high voltage, resulting in surface instability and forming Co3O4 in spinel phase, hindering the diffusion of lithium ions, affecting the magnification and storage performance, and at the same time it is easy to produce by-products and gas production, reducing material performance.
Using a double-clad layer structure, the first cladding layer is obtained by in-situ composite fast ion conductor cladding layer and carbon nanotube composite to obtain, improve the contact between the surface cladding layer and the substrate, and the metal compound layer is used as the second cladding layer to balance the diffusion rate of the electronic conductor and the ionic conductor, and form an inert layer to buffer the damage of the electrolyte.
It improves the diffusion rate of lithium ions, improves the rate performance and storage performance, reduces the generation and diffusion impedance of by-products, extends the cycle life of the material and increases capacity.
Smart Images

Figure CN115966700B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, in particular to a lithium cobalt oxide positive electrode material and a preparation method thereof. Background Art
[0002] Increasing voltage has always been the main development direction of lithium cobalt oxide. Under high voltage, lithium cobalt oxide is very easy to react with the electrolyte, which has a relatively bad effect. Among them, the rate, storage and gas production in the electrochemical performance are greatly challenged. The main reason for the decline of electrochemical performance is the result of the reaction between the surface of lithium cobalt oxide and the electrolyte. Deep delithiation causes Co 3+ →Co 4 + , an irreversible phase transition (CoO2→Co3O4 / CoO) occurs on the surface, and spinel Co3O4 is formed on the surface. The formation and accumulation of spinel Co3O4 hinders the Li + The diffusion of lithium ions affects the transmission of lithium ions, resulting in the deterioration of the material's rate and storage performance. Phase change will lead to the formation of cracks and the crushing of particles, further deteriorating the performance of the material. Under high voltage, lithium cobalt oxide interacts with the electrolyte. In a highly ionized state, LCO is more likely to form oxygen vacancies, release lattice oxygen, and produce more gas. Therefore, the stability of the lithium cobalt oxide interface is very important.
[0003] The co-coating of fast ion conductors and metal compounds can effectively protect the surface of the material. Coating fast ion conductors can improve the ion conductivity of the material and provide a channel for the diffusion of lithium ions; coating metal compounds can provide higher electronic conductivity and improve rate performance. At the same time, most metal compounds are inert. After coating with lithium cobalt oxide, they can better block the erosion of the electrolyte, which is beneficial to gas production. However, at present, co-coating does not take into account the surface contact problem between the substrate and the coating layer. Most fast ion conductors have large particle sizes and poor contact with the surface. The uniformity of the coating also needs to be confirmed. In addition, the polarization effect between the fast ion conductor and the metal compound is not considered. Therefore, it is very important to design a positive electrode material that improves the contact between the fast ion conductor and the electronic conductor and the surface, while reducing the polarization between the materials. Summary of the invention
[0004] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a double-coated lithium cobalt oxide positive electrode material and a preparation method thereof. The present invention uses a method for modifying the substrate of the positive electrode material of a lithium ion battery by in-situ composite fast ion conductor coating layer, and the fast ion conductor and carbon nanotubes CNTs are composited to obtain a first coating layer, thereby obtaining a positive electrode material that improves the contact between the surface coating layer and the substrate and improves the electronic conductor and ion conductor. By composite the second coating layer, the diffusion rate between the electronic conductor and the ion conductor is balanced, the polarization of the battery cell is reduced, and an inert layer is formed on the surface, which buffers the damage of the electrolyte to the coating layer, reduces the generation of by-products, and reduces the diffusion impedance.
[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a lithium cobalt oxide positive electrode material, including a substrate and a coating layer, the coating layer includes a first coating layer and a second coating layer, the first coating layer is coated on the outside of the substrate, and the second coating layer is coated on the outside of the first coating layer; the first coating layer is a fast ion conductor structure LiABO4 coated carbon nanotube, A is a trivalent metal, and B is a tetravalent metal; the second coating layer is a metal compound layer, the metal element in the metal compound is one of Al, Y, Mo, Mg, Zn, W, Zr, Ce, and the chemical formula of the substrate is Li 1+x Co 1-y M y O2, 0≤x≤0.1, 0<y≤0.1, wherein M is at least one of Mg, Co, Ni, Mn, Al, Ti, Ge, La, Ba, Zr, Y, V, W, Nb, Cu, B, Sr, Ga, Zn, Mo, Si, Sb, Ca, and Ta; the metal elements of the second coating layer cannot overlap with the metal elements of the first coating layer.
[0006] The fast ion conductor and carbon nanotubes CNTs of the present invention are composited to obtain the first coating layer, and CNTs have a large specific surface area, which improves the uniformity of the coating and improves the contact between the fast ion conductor and the positive electrode substrate. CNTs have good electronic conductivity, and the first coating layer is a coating layer in which the electronic conductor and the ions act synergistically, wherein the fast ions provide ion diffusion channels between the substrate and the coating layer, and improve the diffusion rate of lithium ions, and CNTs provide electron diffusion channels between the substrate and the coating layer, and improve the diffusion rate of electrons, and the fast ion conductor grows on the surface and inside of the CNTs. CNTs have flexibility and good mechanical stress, and can slow down the damage to the surface layer of the material caused by the insertion and removal of lithium ions at high voltage, and improve the storage performance of the material. The inclusion of CNTs in the coating layer can reduce the use of conductive agents in the battery preparation process, increase the amount of active substances, and thus increase the capacity.
[0007] The second coating layer of the present invention is a metal compound layer, such as oxides, hydroxides, chlorides and organic metal compounds of any one of Al, Y, Mo, Mg, Zn, W, Zr and Ce. Also called an inert coating layer, it balances the diffusion rate between the electronic conductor and the ion conductor, and forms an inert layer on the surface, buffering the damage of the electrolyte to the coating layer, reducing the generation of by-products and reducing the diffusion impedance.
[0008] Preferably, the trivalent metal is one of Ga, W, Y, Cr, La, Eu, Ce, and Er, and the tetravalent metal is one of Ti, Zr, Sn, Ru, Ce, and Mn.
[0009] The introduction of the trivalent metal of the present invention is conducive to improving the stability of the Co-O layer structure, stabilizing the circulation of the electrode material, and increasing the hydrophilicity of the fast ion conductor, which is conducive to the rapid electrochemical reaction between the electrolyte and the electrode, and also promotes the transfer of charge. The introduction of the tetravalent metal of the present invention can reduce the mechanical stress of Co-O, and has good anti-corrosion performance, which can reduce the corrosion effect of HF in the electrolyte on the material.
[0010] Further preferably, the trivalent metal is one of Ga, W, Y, and La, and the tetravalent metal is one of Ti, Zr, and Sn. More preferably, the trivalent metal is Ga, and the tetravalent metal is Zr.
[0011] The inventors found in the actual experimental process that the lithium cobalt oxide positive electrode material prepared by selecting the above elements has better storage and gas production performance and has higher capacity and rate.
[0012] Preferably, the coating layer has a thickness of 30-50 nm.
[0013] The inventors found in actual experiments that when the thickness of the coating layer is 30-50 nm, the prepared lithium cobalt oxide positive electrode material has good storage and gas production performance as well as high capacity and rate. Within the above range, the performance difference is not large.
[0014] In addition, the present invention provides a method for preparing the lithium cobalt oxide positive electrode material, comprising the following steps:
[0015] (1) Preparation of lithium cobalt oxide matrix material Li 1+x Co 1-y M y O2;
[0016] (2) mixing the lithium cobalt oxide matrix material, carbon nanotubes, lithium source, trivalent metal compound, tetravalent metal compound, chelating agent and water to obtain a composite gel;
[0017] (3) calcining the composite gel under an inert gas to obtain a base material coated with a first coating layer;
[0018] (4) calcining the base material coated with the first coating layer and the metal compound under an inert gas to obtain the lithium cobalt oxide positive electrode material.
[0019] Preferably, in step (2), the mass ratio of lithium cobalt oxide matrix material, carbon nanotubes, lithium source, trivalent metal compound, tetravalent metal compound, chelating agent and water is: lithium cobalt oxide matrix material: carbon nanotubes: lithium source: trivalent metal compound: tetravalent metal compound: chelating agent: water = 1: (0.0001-0.001): (0.001-0.002): (0.002-0.005): (0.002-0.005): (0.3-0.8): (2-5).
[0020] Preferably, in step (2), the chelating agent is at least one of ammonia water, salicylic acid and citric acid.
[0021] Preferably, in step (3), the calcination temperature is 450-550°C, and the calcination time is 5-7h; in step (4), the calcination temperature is 250-350°C, and the calcination time is 1.5-2.5h, and the mass ratio of the base material and the metal compound coated with the first coating layer is 1:0.0003-0.0005.
[0022] Furthermore, the present invention provides the use of the lithium cobalt oxide positive electrode material in the preparation of lithium ion batteries.
[0023] Compared with the prior art, the beneficial effects of the present invention are: the lithium cobalt oxide positive electrode material prepared by the present invention has good storage and gas production performance and has a higher capacity and rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a SEM image of the lithium cobalt oxide positive electrode material prepared in Example 1;
[0025] Figure 2 This is the SEM image of the lithium cobalt oxide positive electrode material prepared in Comparative Example 1. DETAILED DESCRIPTION
[0026] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings.
[0027] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0028] Examples 1-9 and Comparative Examples 1-4
[0029] The present invention provides embodiments 1-9 and comparative examples 1-4. The element selection in the process of preparing the first coating layer, the second coating layer and the substrate of the lithium cobalt oxide positive electrode material of specific embodiments 1-9 and comparative examples 1-4 is shown in Table 1.
[0030] Table 1
[0031]
[0032] Example 1
[0033] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiGaZrO4·Al2O3 is as follows:
[0034] (1) Preparation of lithium cobalt oxide matrix material Li 1.045 Co 0.99 Y 0.01 O2; According to the lithium cobalt oxide matrix material Li 1.045 Co 0.99 Y 0.01 The molar ratio of metal in O2 is to weigh corresponding contents of lithium carbonate, cobalt oxide and yttrium oxide, mix them uniformly, sinter them at 1070°C for 8 hours, sinter them in an oxygen atmosphere, and crush them to obtain a lithium cobalt oxide matrix;
[0035] (2) The lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, gallium nitrate, zirconium dioxide, citric acid and water are uniformly mixed to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: gallium nitrate: zirconium dioxide: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.002: 0.5: 3; the mass of the lithium cobalt oxide matrix material is 2 kg;
[0036] (3) The composite gel was placed in a box furnace and calcined under an inert gas N2 at a flow rate of 10 m 3 / h, the calcination temperature is 500°C, the calcination is 6 hours, and the material is crushed by mechanical grinding to obtain a base material coated with the first coating layer;
[0037] (4) The base material coated with the first coating layer and the Al(OH)3 sol are mixed by Kawada spraying, the mass ratio of the base material of the first coating layer to the Al(OH)3 sol is 1:0.0004, and calcined under inert gas N2, sintered at 280°C for 2 hours, to obtain the lithium cobalt oxide positive electrode material Li 1.045 Co 0.99 Y 0.01 O2@CNTs-LiGaZrO4·Al2O3.
[0038] Example 2
[0039] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiWZrO4·Al2O3 is as follows:
[0040] Compared with Example 1, Example 2 only differs in the raw materials used in step (2), and the mass ratio of the raw materials used is the same, and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0041] Specifically, in step (2), the lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, tungsten trioxide, zirconium dioxide, citric acid and water are uniformly mixed to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: tungsten trioxide: zirconium dioxide: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.002: 0.5: 3; and the mass of the lithium cobalt oxide matrix material is 2 kg.
[0042] Example 3
[0043] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiLaZrO4·Al2O3 is as follows:
[0044] Compared with Example 1, Example 3 only uses different raw materials in step (2), and the mass ratio of the raw materials used is the same, and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0045] Specifically, in step (2), the lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, lanthanum nitrate, zirconium dioxide, citric acid and water are uniformly mixed to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: lanthanum nitrate: zirconium dioxide: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.002: 0.5: 3; and the mass of the lithium cobalt oxide matrix material is 2 kg.
[0046] Example 4
[0047] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiGaTiO4·Al2O3 is as follows:
[0048] Compared with Example 1, Example 4 only differs in the raw materials used in step (2), and the mass ratio of the raw materials used is the same, and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0049] Specifically, in step (2), the lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, gallium nitrate, titanium dioxide, citric acid and water are uniformly mixed to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: gallium nitrate: titanium dioxide: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.002: 0.5: 3; and the mass of the lithium cobalt oxide matrix material is 2 kg.
[0050] Example 5
[0051] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiGaSnO4·Al2O3 is as follows:
[0052] Compared with Example 1, Example 5 only uses different raw materials in step (2), and the mass ratio of the raw materials used is the same, and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0053] Specifically, in step (2), the lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, gallium nitrate, tin oxide, citric acid and water are uniformly mixed to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: gallium nitrate: tin oxide: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.002: 0.5: 3; the mass of the lithium cobalt oxide matrix material is 2 kg.
[0054] Example 6
[0055] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiCeSiO4·Al2O3 is as follows:
[0056] Compared with Example 1, Example 6 only uses different raw materials in step (2), and the mass ratio of the raw materials used is the same, and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0057] Specifically, in step (2), the lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, cerium hydroxide, zirconium dioxide, citric acid and water are uniformly mixed to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: cerium hydroxide: zirconium dioxide: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.002: 0.5: 3; the mass of the lithium cobalt oxide matrix material is 2 kg.
[0058] Example 7
[0059] Lithium cobalt oxide cathode material Li1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiGaMnO4·Al2O3 is as follows:
[0060] Compared with Example 1, Example 7 only uses different raw materials in step (2), and the mass ratio of the raw materials used is the same, and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0061] Specifically, in step (2), the lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, gallium nitrate, manganese dioxide, citric acid and water are uniformly mixed to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: gallium nitrate: manganese dioxide: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.002: 0.5: 3; and the mass of the lithium cobalt oxide matrix material is 2 kg.
[0062] Example 8
[0063] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiGaMnO4·MgO is as follows:
[0064] Compared with Example 1, Example 8 only differs in the raw materials used in step (4), and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0065] Specifically, (4) the base material coated with the first coating layer and the Mg(OH)2 sol are mixed by Kawada spraying at a mass ratio of 1:0.0004, calcined under inert gas N2, and sintered at 280°C for 2 hours to obtain the lithium cobalt oxide positive electrode material.
[0066] Example 9
[0067] Lithium cobalt oxide cathode material Li 1.05 Co 0.95 La 0.05 The preparation method of O2@CNTs-LiGaZrO4·Al2O3 is as follows:
[0068] Compared with Example 1, Example 9 differs only in the raw materials used for preparing the substrate in step (1), and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0069] Specifically, (1) preparing the lithium cobalt oxide matrix material Li 1.05 Co 0.95 La 0.05 O2; According to the lithium cobalt oxide matrix material Li 1.05 Co 0.95 La 0.05The molar ratio of metal in O2 is obtained by weighing corresponding amounts of lithium carbonate, cobalt oxide and lanthanum nitrate, mixing them evenly, sintering them at 1070°C for 8 hours, sintering them in an oxygen atmosphere, and crushing them to obtain a lithium cobalt oxide matrix.
[0070] Comparative Example 1
[0071] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@LiGaZrO4·Al2O3 is as follows:
[0072] Compared with Example 1, Comparative Example 1 differs only in the process of preparing the composite gel in step (2), and the rest of the preparation processes, raw material selection, etc. are exactly the same.
[0073] Specifically, (2) the lithium cobalt oxide matrix material, lithium acetate, gallium nitrate, zirconium dioxide, citric acid and water are mixed evenly to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: lithium acetate: gallium nitrate: zirconium dioxide: citric acid: water = 1: 0.002: 0.004: 0.002: 0.5: 3; the mass of the lithium cobalt oxide matrix material is 2 kg.
[0074] Comparative Example 2
[0075] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiGaZrO4 is as follows:
[0076] Compared with Example 1, Comparative Example 2 does not perform step (4), and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0077] Specifically, (1) preparing the lithium cobalt oxide matrix material Li 1.045 Co 0.99 Y 0.01 O2; According to the lithium cobalt oxide matrix material Li 1.045 Co 0.99 Y 0.01 The molar ratio of metal in O2 is to weigh the corresponding content of lithium carbonate, cobalt oxide, and yttrium oxide, and mix them evenly, sinter them at 1070°C for 8 hours, sinter them in an oxygen atmosphere, and crush them to obtain a lithium cobalt oxide matrix;
[0078] (2) The lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, gallium nitrate, zirconium dioxide, citric acid and water are uniformly mixed to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: gallium nitrate: zirconium dioxide: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.002: 0.5: 3; the mass of the lithium cobalt oxide matrix material is 2 kg;
[0079] (3) The composite gel was placed in a box furnace and calcined under an inert gas N2 at a flow rate of 10 m 3 / h, the calcination temperature is 500°C, the calcination is for 6 hours, and the material is crushed by mechanical grinding to obtain a base material coated with the first coating layer, that is, the lithium cobalt oxide positive electrode material.
[0080] Comparative Example 3
[0081] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-LiGaO2·Al2O3 is as follows:
[0082] Compared with Example 1, Comparative Example 3 differs only in the process of preparing the composite gel in step (2), and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0083] Specifically, (2) the lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, gallium nitrate, citric acid and water are mixed evenly to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: gallium nitrate: citric acid: water = 1: 0.0005: 0.002: 0.004: 0.5: 3; the mass of the lithium cobalt oxide matrix material is 2 kg.
[0084] Comparative Example 4
[0085] Lithium cobalt oxide cathode material Li 1.045 Co 0.99 Y 0.01 The preparation method of O2@CNTs-Li2ZrO3·Al2O3 is as follows:
[0086] Compared with Example 1, Comparative Example 5 differs only in the process of preparing the composite gel in step (2), and the rest of the preparation process, raw material selection, etc. are exactly the same.
[0087] Specifically, (2) the lithium cobalt oxide matrix material, carbon nanotubes, lithium acetate, zirconium dioxide, citric acid and water are mixed evenly to obtain a composite gel; wherein the mass ratio is lithium cobalt oxide matrix material: carbon nanotubes: lithium acetate: zirconium dioxide: citric acid: water = 1: 0.0005: 0.002: 0.002: 0.5: 3; the mass of the lithium cobalt oxide matrix material is 2 kg.
[0088] Performance Testing
[0089] Electrochemical performance test: The lithium cobalt oxide positive electrode material, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) prepared in the embodiments of the present invention and the comparative examples are mixed in a mass ratio of 92:4:4, N-methylpyrrolidone (NMP) is added, and the mixture is stirred to form a slurry, which is then coated on an aluminum foil, dried at 100°C, and rolled and cut into positive electrode sheets; graphite, conductive carbon black (SuperP), styrene-butadiene rubber (SBR), and sodium carboxymethyl cellulose (CMC) are mixed in a mass ratio of 94:1:2.5:2.5, deionized water is added, the mixture is formed into a slurry, which is then coated on a copper foil, dried at 80°C, and rolled and cut into negative electrode sheets; the positive electrode sheet, the separator, and the negative electrode sheet are wound into a soft-pack battery cell, which is aged and capacitated after being injected with the electrolyte, and then the electrochemical performance test is performed.
[0090] Rate test conditions: 25℃, charge and discharge voltage window is 3.0-4.48V, the battery is charged at 1C constant current and constant voltage (cut-off current 0.025C), discharged at 1C constant current, then charged at 3C constant current and constant voltage, discharged at 3C constant current, 3C discharge rate = 3C discharge capacity / 1C discharge initial capacity*100%.
[0091] Cycle test conditions: 45°C, charge and discharge voltage window 3.0-4.48V, battery charged at 1C (cut-off current 0.025C), discharged at 1C, discharge retention rate = discharge capacity / charge capacity*100%, when the discharge retention rate is 80% corresponding to the discharge cycle.
[0092] Storage test conditions: the battery cells were fixed in capacity before storage, and after storage at 60°C, the capacity retention rate and capacity recovery were tested every 7 days with the charge and discharge voltage window between 3.0-4.48V at 25°C. Capacity retention rate = first discharge capacity after full-charge storage / last discharge capacity before full-charge storage * 100%, capacity recovery rate = second discharge capacity after storage / last discharge capacity before storage.
[0093] Gas production test conditions: fully charged cells are stored at 60°C. After the cells are cooled down at 25°C periodically, the cell volume is tested and the volume growth is calculated by the water displacement method.
[0094] Test results: as shown in Table 2.
[0095] Table 2
[0096]
[0097] As can be seen from the above table, the lithium cobalt oxide positive electrode materials prepared in Examples 1-9 of the present invention have advantages in rate, cycle, storage and gas production by using double-layer coating. The fast ion conductor and carbon nanotubes CNTs are composited to obtain the first coating layer. CNTs have a large specific surface area, which improves the uniformity of the coating and improves the contact between the fast ion conductor and the positive electrode substrate. In coordination with the metal compound layer, i.e., the second coating layer, the diffusion rate between the electronic conductor and the ion conductor is balanced, the damage of the electrolyte to the coating layer is buffered, the generation of by-products is reduced, and the diffusion impedance is reduced.
[0098] From the comparison of the embodiments, it can be seen that the selection of the elements of the first coating layer has a great influence on the storage, gas production performance, capacity and rate of the prepared lithium cobalt oxide positive electrode material. When the trivalent metal is Ga and the tetravalent metal is Zr, the 3C retention rate of the prepared lithium cobalt oxide positive electrode material is more than 90%, the 45°C cycle retention rate is 80% for 850 weeks, the 60°C storage recovery rate is 83.6% for 28 days, and the gas production at 60°C is 1.25 ml / Ah.
[0099] From the comparison between Example 1 and Comparative Examples 1-4, it can be seen that the double-layer coating of the present invention is indispensable, and the fast ion conductor structure LiABO4 of the first coating layer, in which A is a trivalent metal and B is a tetravalent metal, is also indispensable. Under the specific coating of the present invention, the prepared lithium cobalt oxide positive electrode material has advantages in rate, cycle, storage and gas production.
[0100] Figure 1 This is a SEM image of the lithium cobalt oxide positive electrode material sample prepared in Example 1. It can be seen from the image that the surface of the material is obviously wrapped with CNTs. The CNTs have flexibility and good mechanical stress, which can provide good protection for the surface of the material, and together with the second layer of coating, form a good surface coating structure layer; Figure 2 This is the SEM image of the lithium cobalt oxide positive electrode material sample prepared in Comparative Example 1. From the image, it can be seen that there is an obvious coating layer and the CNTs composite is missing. The rate, cycle, storage and gas production performance of the material are significantly reduced.
[0101] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A lithium cobalt oxide positive electrode material, characterized in that: The invention comprises a substrate and a coating layer, wherein the coating layer comprises a first coating layer and a second coating layer, the first coating layer is coated outside the substrate, and the second coating layer is coated outside the first coating layer; the first coating layer is a fast ion conductor structure LiABO4 coated carbon nanotube, wherein A is a trivalent metal, and B is a tetravalent metal, wherein the trivalent metal is one of Ga, W, and La, and the tetravalent metal is one of Ti, Zr, Sn, and Mn; wherein the fast ion conductor grows on the surface and inside of the CNTs; the second coating layer is a metal compound layer, wherein the metal element in the metal compound is one of Al, Y, Mo, Mg, Zn, W, Zr, and Ce, and the chemical formula of the substrate is Li 1+x Co 1-y M y O2, 0≤x≤0.1, 0<y≤0.1, wherein M is at least one of Mg, Co, Ni, Mn, Al, Ti, Ge, La, Ba, Zr, Y, V, W, Nb, Cu, B, Sr, Ga, Zn, Mo, Si, Sb, Ca, and Ta; the metal elements of the second coating layer cannot overlap with the metal elements of the first coating layer.
2. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The trivalent metal is Ga, and the tetravalent metal is Zr.
3. The lithium cobalt oxide positive electrode material according to claim 1, characterized in that The coating layer has a thickness of 30-50 nm.
4. A method for preparing a lithium cobalt oxide positive electrode material according to any one of claims 1 to 3, characterized in that: The steps include: (1) Preparation of lithium cobalt oxide matrix material Li 1+x Co 1-y M y O2; (2) mixing the lithium cobalt oxide matrix material, carbon nanotubes, lithium source, trivalent metal compound, tetravalent metal compound, chelating agent and water to obtain a composite gel; (3) calcining the composite gel under an inert gas to obtain a base material coated with a first coating layer; (4) calcining the base material coated with the first coating layer and the metal compound under an inert gas to obtain the lithium cobalt oxide positive electrode material.
5. The method for preparing the lithium cobalt oxide positive electrode material according to claim 4, characterized in that: In the step (2), the mass ratio of the lithium cobalt oxide matrix material, carbon nanotubes, lithium source, trivalent metal compound, tetravalent metal compound, chelating agent and water is: lithium cobalt oxide matrix material: carbon nanotubes: lithium source: trivalent metal compound: tetravalent metal compound: Chelating agent: water = 1: (0.0001-0.001): (0.001-0.002): (0.002-0.005): (0.002-0.005): (0.3-0.8): (2-5).
6. The method for preparing a lithium cobalt oxide positive electrode material according to claim 4, characterized in that: In the step (2), the chelating agent is at least one of ammonia water, salicylic acid and citric acid.
7. The method for preparing a lithium cobalt oxide positive electrode material according to claim 4, characterized in that: In the step (3), the calcination temperature is 450-550° C., and the calcination time is 5-7 hours; in the step (4), the calcination temperature is 250-350° C., and the calcination time is 1.5-2.5 hours.
8. Use of the lithium cobalt oxide positive electrode material according to any one of claims 1 to 3 in the preparation of lithium ion batteries.
Citation Information
Patent Citations
Double-coating-layer modified lithium ion battery positive electrode material and preparation method thereof
CN112349905A
Positive electrode material, electrochemical device comprising same, and electronic device
CN114068889A